Răspuns :
(x+4)/6 +(2x-7)/3= 1 + (4-3x)/2 aducem la acelasi numitor
x+4+4x-14=6 + 12-9x
5x-10= -9x +18
5x+9x=18-10
14x=8
x= 8/14= 2/7
x+4+4x-14=6 + 12-9x
5x-10= -9x +18
5x+9x=18-10
14x=8
x= 8/14= 2/7
[tex] \frac{x + 4}{6} + \frac{2x - 7}{3} = 1 + \frac{4 - 3x}{2} [/tex]
Aducem la acelasi numitor.
[tex] \frac{x + 4}{6} + \frac{2(2x-7)}{6} = \frac{6}{6} + \frac{3(4-3x)}{6} [/tex]
[tex]x + 4 + 4x - 14 = 6 + 12 - 9x[/tex]
[tex]x + 4x + 9x = 6 + 12 + 14 - 4[/tex]
[tex]14x = 28[/tex]
[tex]x = \frac{28}{14} = 2[/tex]
Aducem la acelasi numitor.
[tex] \frac{x + 4}{6} + \frac{2(2x-7)}{6} = \frac{6}{6} + \frac{3(4-3x)}{6} [/tex]
[tex]x + 4 + 4x - 14 = 6 + 12 - 9x[/tex]
[tex]x + 4x + 9x = 6 + 12 + 14 - 4[/tex]
[tex]14x = 28[/tex]
[tex]x = \frac{28}{14} = 2[/tex]